Motivates that Influence Sharia Accounting Students to Become Auditors - Rahmasari, Yusnia; Dyah Pravitasari (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2023)
The purpose of this research is to gather data on factors such as accounting knowledge, professional training, market considerations, and ethical scandals related to the interest of Sharia accounting students in pursuing a career as auditors. This research employs a quantitative approach with purposive sampling as the method of data collection, primarily through surveys. The data is analyzed using descriptive statistics, data testing, classical assumptions, and hypothesis testing techniques. The findings of the research indicate that factors such as accounting knowledge, professional training, and ethical scandals have an impact on the desire of Sharia accounting students to become auditors. However, the variable of market considerations does not influence the willingness of Sharia accounting students to pursue a career as auditors. This research contributes to the field by shedding light on the motivations and influences that drive Sharia accounting students to choose a career as auditors. It adds valuable insights into the factors that impact their career choices within the context of ethical considerations and professional development.